Early Epigenetic Responses in the Genomic DNA Methylation Fingerprints in Cells in Response to Sublethal Exposure of Silver Nanoparticles - Chen, Yue; Sheng, Fei; Wang, Xingyu; Zhang, Zhihong; Qi, Shiyong; Chen, Liqun (Frontiers in Bioengineering and Biotechnology, 2022)
With the rapid development of nanotechnology and nanoscience, nanosafety assessment has raised public concern. Although many studies have illustrated that nanomaterials could lead to genotoxicity, the early alterations of DNA methylation with nanomaterials under low-dose exposure have not been completely clear. In this study, we investigated the potential effect and molecular mechanism of AgNPs on the alternation of DNA methylation fingerprints in HEK293T cells under sublethal exposure. Intriguingly, silver nanoparticle treatment increased 5-mC level and changed methylation-related enzyme contents. Mechanistically, we scrutinized the changes in the molecular signaling and biological functions by means of MeDIP-Seq and RNA-seq. Our results revealed that AgNPs might undermine a number of vital regulatory networks including the metabolic processes, biological regulation and other cellular processes. More specifically at the DNA methylation fingerprints, there were 12 up-regulated and simultaneous hypomethylated genes, and 22 down-regulated and concomitant hypermethylated genes in HEK293T cells responding to AgNPs. Notably, these genes were primarily involved in lipid metabolism and ion metabolism. Together, these responsive genes might be used as early sensitive indicators for the variations of early epigenetic integrity through changing the DNA methylation fingerprints, as reflective of biological risk and toxicity of silver nanoparticles under realistic exposure scenarios.